Pengaruh Jual Beli Online dan Jual Beli di Pasar terhadap Persaingan Pemasaran Islam Masa Pandemi - Siti Hofifah (Prodi Perbankan Syariah, Fakultas Ekonomi dan Bisnis Islam, Universitas Al Hikmah Indonesia, 2020)
The form of the problem in this journal is the finding of problems in product marketing competition between online buying and selling and buying and selling in the market during the pandemic period, where most producers experienced a decline in income. This is due to the emergence of the Covid-19 outbreak. So that producers must have and know how to get enthusiasm from consumers, increase turnover, and know the advantages and disadvantages of buying and selling online and buying and selling in the market so that producers get maximum results. The purpose of this journal is to find out how to get enthusiasm from consumers, to find out how to increase turnover, and to find out the advantages and disadvantages of buying and selling online and buying and selling in the market. This research is a qualitative research. The research technique used is a questionnaire. Keywords: Marketing, Online Buying and Selling, Market